2016
DOI: 10.1097/01.ogx.0000511202.23878.e3
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Germline Inheritance of Diet-Induced Obesity and Insulin Resistance

Abstract: (Abstracted from Nat Genet 2016;48:497–499) Several genetic risk factors for diabetes and obesity have been identified. In addition to genetic risk factors, it has been proposed that epigenetic alterations in gametes are another potential mechanism of disease risk inheritance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 0 publications
2
38
0
2
Order By: Relevance
“…However, Masuyama et al reported no difference in body weight from 4 to 16 weeks of age, followed by increased body weight and homeostatic model assessment of insulin resistance at 24 weeks of age in male offspring from fathers fed a 62% fat diet . Moreover, using in vitro fertilization, Huypens et al found that sperm isolated from F0 mice fed a 60% fat diet did not induce changes in body weight or glucose tolerance in male offspring at 14 weeks of age . In our study, using a mouse model of paternal obesity induced by a 60% fat diet, we also found no differences in body weight or blood metabolic parameters in male offspring at 8 weeks of age.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…However, Masuyama et al reported no difference in body weight from 4 to 16 weeks of age, followed by increased body weight and homeostatic model assessment of insulin resistance at 24 weeks of age in male offspring from fathers fed a 62% fat diet . Moreover, using in vitro fertilization, Huypens et al found that sperm isolated from F0 mice fed a 60% fat diet did not induce changes in body weight or glucose tolerance in male offspring at 14 weeks of age . In our study, using a mouse model of paternal obesity induced by a 60% fat diet, we also found no differences in body weight or blood metabolic parameters in male offspring at 8 weeks of age.…”
Section: Discussionsupporting
confidence: 59%
“…However, there are differential effects of paternal obesity on offspring phenotype across different mouse models. For example, Fullston et al showed that paternal exposure to a 40% fat diet increased body weight and impaired glucose tolerance in male offspring from 8 weeks of age onward (33 (35). In our study, using a mouse model of paternal obesity induced by a 60% fat diet, we also found no differences in body weight or blood metabolic parameters in male offspring at 8 weeks of age.…”
Section: Discussionsupporting
confidence: 55%
“…Unfortunately, it found no association between paternal obesity and risk of CP in children . However, recent studies have found that a parental high‐fat diet mouse model renders offspring more susceptible to developing diabetes and obesity in a sex and parent of origin–specific mode by using in vitro fertilization to ensure exclusive inheritance via the gametes . Therefore, paternal obesity should be an important confounding factor for the risk of CP in children with obese mothers.…”
Section: Discussionmentioning
confidence: 99%
“…We previously found specific perturbations relating to fertilization, blastocyst formation, and implantation using our published mouse model of paternal obesity, which was achieved through diet‐induced obesity in males (Bakos, Mitchell, Setchell, & Lane, ; Mitchell, Bakos, & Lane, ; Binder, Mitchell, & Gardner, ; McPherson, Bakos, Owens, Setchell, & Lane, ). Importantly, our mouse model transmitted aberrant glucose metabolism as well as adiposity to the F1 and F2 generations (Fullston et al, , ); this generation‐spanning phenotype was recently confirmed in a mouse model using in vitro fertilization (Huypens et al, ). These data together support the hypothesis that aberrant regulation of factors controlling gene expression—including epigenetic deregulation—is initiated during spermatogenesis.…”
Section: Introductionmentioning
confidence: 54%